Pre-Hospital Handling in the Community, a Qualitative Research: Qualitative Research - Wiseno, Bambang; Mohammad Ikhwan Khosasih; Fajar Rinawati; Didik Susetiyanto Atmojo; Elfi Quyumi Rahmawati; Dwi Rahayu (Journal Of Nursing Practice, 2025)
Background: Emergency handling before transferring to the hospital (Pre-Hospital treatment) determines the success of emergency case handling. That’s actions include; emergency and non-emergency evacuation and first aid escort in the community. Pre-hospital treatment can be carried out by anyone who is around the location of the emergency at the time of the incident. This treatment aims to identify clients and to provide immediate action needed before being sent to health services. Ordinary people who are around the incident sometimes take actions that worsen the client's condition because of their knowledge and/or abilities. Purpose: This study aims to determine the perspective of the ordinary community on Pre-Hospital treatment for emergency incidents in the community. Methods: This qualitative study was conducted by interviewing (in-depth-interview) the ordinary community as Informant with purposive sampling in Pelem Village, Pare District, Kediri Regency, Indonesia who willing to be informants in this study. Data analysis used Interpretative Phenomenology Analysis with validity through data triangulation and conducting peer-debriefing with other qualitative researchers. Results: From this study, several findings of the theme were obtained, including; lack of understanding of residents about pre-hospital actions, wrong actions, feeling pre-hospital knowledge for public, need for the role of the media, hoping for health workers in each region, helping villagers. Conclusion: From all the themes, it is possible that there needs to be health education for the general public, especially about pre-hospital treatment to prevent the severity of wrong actions. Increasing knowledge about health needs to be done continuously at the community.